The actin filament-severing domain of plasma gelsolin (The Rockefeller University Press, 1986)
Gelsolin, a multifunctional actin-modulating protein, has two actin- binding sites which may interact cooperatively. Native gelsolin requires micromolar Ca2+ for optimal binding of actin to both sites, and for expression of its actin filament-severing function. Recent work has shown that an NH2-terminal chymotryptic 17-kD fragment of human plasma gelsolin contains one of the actin-binding sites, and that this fragment binds to and severs actin filaments weakly irrespective of whether Ca2+ is present. The other binding site is Ca2+ sensitive, and is found in a chymotryptic peptide derived from the COOH-terminal two- thirds of plasma gelsolin; this fragment does not sever F-actin or accelerate the polymerization of actin. This paper documents that larger thermolysin-derived fragments encompassing the NH2-terminal half of gelsolin sever actin filaments as effectively as native plasma gelsolin, although in a Ca2+-insensitive manner. This result indicates that the NH2-terminal half of gelsolin is the actin-severing domain. The stringent Ca2+ requirement for actin severing found in intact gelsolin is not due to a direct effect of Ca2+ on the severing domain, but indirectly through an effect on domains in the COOH-terminal half of the molecule to allow exposure of both actin-binding sites.